2017
DOI: 10.1080/87565641.2017.1414821
|View full text |Cite
|
Sign up to set email alerts
|

Systematic overview of neuroanatomical differences in ADHD: Definitive evidence

Abstract: ADHD symptoms might be due to a multi-network unbalanced functioning hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 89 publications
(157 reference statements)
3
7
0
6
Order By: Relevance
“…Importantly, we found no differences in local gray matter distribution, which is in line with the systematic review by de Melo et al 19 . The authors analyzed 17 reviews of whom none reported structural changes in adults with ADHD, while changes were reported in ADHD children.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Importantly, we found no differences in local gray matter distribution, which is in line with the systematic review by de Melo et al 19 . The authors analyzed 17 reviews of whom none reported structural changes in adults with ADHD, while changes were reported in ADHD children.…”
Section: Discussionsupporting
confidence: 93%
“…It is of note that a recent placebo-controlled double-blind fMRI study, testing the comparative neurofunctional effects of methylphenidate and atomoxetine during sustained attention, showed normalization in right fronto-parietal-thalamic areas under methylphenidate, but not under placebo 23 . In line with these findings, in the current study the associations between NET availability in right fronto-parietal-thalamic-cerebellar regions and neuropsychological and neurophysiological parameters, suggest a pathophysiological role of NET availability in adult ADHD and support the model of right hemisphere deficits 19,57 in ADHD. While brain arousal has been understood as a generalized state of the brain 58 , it is a consistent finding that the ability to maintain an alert state relies heavily on the right cerebral hemisphere 14,59,60 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Anatomical magnetic resonance imaging (MRI) studies have found a small number of consistent findings across the agerange of ADHD (21). Multiple meta-analyses of case-control studies have shown reduced volume of the striatum in children with ADHD (22)(23)(24)(25); however, the reduced striatal volume in ADHD appears to correct itself with age (24,26).…”
Section: Anatomical Mrimentioning
confidence: 99%
“…Ätiologie ADHS ist eine Spektrumstörung, d. h. es gibt eine Vielfalt klinischer Ausprä-gungen, Schweregrade, Komorbiditäten und Verläufe sowie auch eine beträchtliche ätiologische Heterogenität [228,315]. Strukturell finden sich globale Auffälligkeiten, insbesondere verzögerte Hirnentwicklung mit kortikaler Massenreduktion vor allem im Frontalhirn, weiterhin thalamikale und zerebelläre Strukturdefizite, Vernetzungsprobleme langer Bahnen [332] sowie Mikrostrukturanomalien frontal, temporal und parietal [7,112,267,330]. Funktionelle Defizite betreffen Aktivierung und Konnektivität in diesen Arealen [125].…”
Section: Ergebnisseunclassified